Does the use of an electronic reminder device with or without counseling improve adherence to lipid-lowering treatment? The results of a randomized controlled trial - Kooy, Marcel J.; Wijk, Boris L.; Boer, Anthonius; Heerdink, Eibert R.; Bouvy, Marcel L. (Frontiers in Pharmacology, 2013)
BACKGROUND: The use of lipid lowering treatment with statins has proven to be effective in reducing cardiovascular events and mortality. However in daily practice adherence to medication is often low and compromises the effect of therapy. The aim of this study was to assess the effectiveness of an electronic reminder device (ERD) with or without counselling to improve refill adherence and persistence to statin treatment in non-adherent patients. METHODS: A multicenter, community pharmacy-based randomized controlled trial conducted in 24 pharmacies in The Netherlands, with patients with prior baseline refill adherence rates between 50-80%. Eligible patients of ≥ 65 years were randomly assigned to 1 of 3 groups: (1) counselling with an ERD (n=134), (2) ERD with a written instruction (n=131) and (3) control group (n=134). MAIN OUTCOME MEASURE: refill adherence to statin treatment in 360 days after inclusion (PDC360). Patients with a refill rate ≥ 80% were considered adherent. We also assessed the effect among subgroups. RESULTS: There were no relevant differences at baseline. In the counselling + ERD-arm 54 of 130 eligible patients received the counselling with ERD. In the ERD-arm, 117 of 123 eligible patients received the ERD. The proportions of adherent patients in the counselling + ERD group (69.2%) and in the ERD-only group (72.4%) were not higher compared to the control group (64.8%). Among women using statins for secondary prevention, in the ERD group more patients were adherent (86.1%) than in the usual care group (52.6%) (p<0.005). In men using statins for secondary prevention, no effect of the ERD has been found. CONCLUSION: In this randomized controlled trial, we found no statistically significant improvement of refill adherence with the use of an ERD with or without counselling. However, in a subgroup of women using statins for secondary prevention, the ERD improved adherence statistically significant.